2018
DOI: 10.29328/journal.jsmt.1001031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of static, dynamic, and pelvic stability in junior badminton players of South Asia

Abstract: Badminton is a sport that requires a player to perform while being still, as well as in motion. Stability is the ability to maintain or control joint movement or joint position, in the static as well as dynamic state. Improvement in stability could help maintain body control and proper posture positions during play. Accordingly, the study was proposed to analyze stability in junior badminton players and understand its importance. A total of 106 players from South Asia between the ages of 8 and 15 years were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Scapular and lumbar load asymmetry has been discussed by the current authors and it could play a role in decreased trunk range of motion Ranawat [11]. There was no significant difference found in hip range of motion while walking or running, however when the same authors tested hip stability and hip musculature in the sitting position, certain differences were found Manan, Digpal, Apoorva, & Manit [30]. There was no significant difference observed between any of the other groups in both, run and gait analysis.…”
Section: Non-modifiable Factorsmentioning
confidence: 75%
See 2 more Smart Citations
“…Scapular and lumbar load asymmetry has been discussed by the current authors and it could play a role in decreased trunk range of motion Ranawat [11]. There was no significant difference found in hip range of motion while walking or running, however when the same authors tested hip stability and hip musculature in the sitting position, certain differences were found Manan, Digpal, Apoorva, & Manit [30]. There was no significant difference observed between any of the other groups in both, run and gait analysis.…”
Section: Non-modifiable Factorsmentioning
confidence: 75%
“…The advantages of balance and stability training too have been highlighted. The authors indicate balance and stability training to be effective for gain in muscular strength and equalization of muscular imbalances Heitkamp, Horstmann, Mayer, Weller, & Dickhuth [31], Manan [30]. Another study showed the concept of hip muscle imbalance being associated with low back pain occurrence in female athletes Nadler [13].…”
Section: Modifiable Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…The muscles around the pelvis may be imbalanced and lead to reduced levels of stability, mobility, flexibility and strength, eventually affecting a player's performance. The importance of pelvic stability has been well highlighted and the need for pelvic stability training to be incorporated in a badminton player's regimen is necessary Manan, Digpal, Apoorva, & Manit [23]. This also shows that despite players having more than 5 years' experience in the sport, they may not have access to strength and conditioning specialists or specialised physiotherapists who can help train them in improving their muscle imbalance and that it is not being given the importance it needs.…”
Section: Non-modifiable Factorsmentioning
confidence: 99%
“…Their research further supported the need for the assessment and treatment of hip muscle imbalance in individuals with low back pain. In a previous study, we assessed hip stability, helping us pinpoint the exact region of muscle imbalance and treat it accordingly Manan et al [23].…”
Section: Modifiable Factorsmentioning
confidence: 99%